2011
DOI: 10.4236/msa.2011.211213
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Characteristics of Ba(Fe<sub>0.5</sub>Nb<sub>0.5</sub>)O<sub>3</sub>-SrTiO<sub>3</sub> Ceramic System

Abstract: A complex structure of barium iron niobate, Ba(Fe 0.5 Nb 0.5)O 3 (BFN) and strontium titanate SrTiO 3 (ST) was fabricated by a solid-state reaction method. The phase formation of Ba(Fe 0.5 Nb 0.5)O 3-SrTiO 3 was checked using X-ray diffraction (XRD) technique. The X-ray structural analysis of BFN and BFN-ST ceramics, showed the formation of single-phase compound in the monoclinic system, which is a distorted structure of an ideal cubic perovskite. Careful examination of microstructures of the individual compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, efforts are being made to lower down the dielectric loss without affecting its dielectric constant. Recently, solid solutions of BFN with BaTiO 3 [2][3][4][5][6][7][8], SrTiO 3 [8][9][10], Ba(Zr,Ti)O 3 [11], PbZr 0.52 Ti 0.48 O 3 [12] have been reported to modify its performance characteristics. It is observed that addition of BT into BFN lower down the dielectric loss of BFN [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts are being made to lower down the dielectric loss without affecting its dielectric constant. Recently, solid solutions of BFN with BaTiO 3 [2][3][4][5][6][7][8], SrTiO 3 [8][9][10], Ba(Zr,Ti)O 3 [11], PbZr 0.52 Ti 0.48 O 3 [12] have been reported to modify its performance characteristics. It is observed that addition of BT into BFN lower down the dielectric loss of BFN [2].…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric study of lead-free ternary compounds has been the focus of researchers in recent years and some interesting results have already been reported [17][18][19][20][21]. Recently, our group has also studied the dielectric relaxation behavior of some A(B′B″)O 3 type perovskite oxides [22][23][24][25][26][27][28][29][30]. In this paper we investigate the structural and dielectric relaxation properties of the strontium gadolinium niobate, Sr-(Gd 0.5 Nb 0.5 )O 3 , (SGN) ceramics in the temperature range from 60˚C to 420˚C and in the frequency 50 Hz to 1 MHz by means of dielectric spectroscopy.…”
Section: Introductionmentioning
confidence: 99%